1991
DOI: 10.1002/food.19910350515
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intestinal resection and type of diet on the digestive and metabolic utilization of fats in rats

Abstract: The effects of the quality of dietary fat, and the influence of ursodeoxycholic acid, an exogenous bile acid, on the digestive and metabolic utilization of fat were studied in rats in which 50% of the distal small intestine was resected. The fat content of the diets was quantitatively equivalent (4%), and differed only in the type of fat: olive oil (diet A) or 1/3 medium chain triglycerides (MCT), 1/3 sunflower oil and 1/3 olive oil (diet B). The removal of 50% of the distal small intestine led to a highly sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This seems to be due to the fact that resected animals tend to satisfy their caloric requirements by increasing food intake and thus compensate for the absence of half of the small intestine. These findings coincide with those of Coves et al (1991). The type of diet given influences intake, and so the goat milk diet is consumed in smaller volumes.…”
Section: Discussionsupporting
confidence: 85%
“…This seems to be due to the fact that resected animals tend to satisfy their caloric requirements by increasing food intake and thus compensate for the absence of half of the small intestine. These findings coincide with those of Coves et al (1991). The type of diet given influences intake, and so the goat milk diet is consumed in smaller volumes.…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that the modification of dietary lipid quality improves the digestive utilization of fat and that this improvement is maintained when ursodeoxycholic acid is added to the diet. Moreover, the fatty acid profile in serum revealed no deficit in essential fatty acids caused by intestinal resection or by type of diet, but did clearly reflect the source of dietary fat [19].…”
Section: Effects Of Dietary Goat Milk On the Nutritive Utilization Ofmentioning
confidence: 99%
“…The resection of 50% of the distal small intestine produces a significant decrease in the amount of fat [6,19,20] due to a diminution in the absorptive surface area and to the greater intestinal transit speed, suggesting there is less contact time between the fat and the mucosa. Moreover, ileal resection creates a severe interruption in enterohepatic circulation, which gives rise to a notable decrease in the production of biliary salts [53], despite increased synthesis of the latter [63], which impedes the absorption of fats [22].…”
Section: Effects Of Dietary Goat Milk On the Nutritive Utilization Ofmentioning
confidence: 99%
See 2 more Smart Citations